Rediscovering Enoch?: the antediluvian past from the fifteenth to nineteenth centuries - Hessayon, Ariel; Reed, Annette Yoshiko; Boccaccini, Gabriele (Studia in Veteris Testamenti Pseudepigrapha Ser., 2023)
Intro -- Contents -- Figures and Tables -- Abbreviations -- Notes on Contributors -- Introduction -- Part 1 European Traditions and Trajectories before James Bruce's "Discovery" and Its Impact -- 1 Enoch Lost and Found?: Rethinking Enochic Reception in the Middle Ages -- 2 The Book of Enoch in Relation to the Premodern Christian Doctrines of Spiritual Beings -- 3 Giovanni Pico della Mirandola, Enoch, and Hermetism -- 4 Earliest Commentaries on 1 Enoch before Laurence: Pompeo Sarnelli (1710) and Daniele Manin (1820) -- 5 Enoch and the Genesis of Freemasonry -- 6 Blake's Enoch before the Book of Enoch -- 7 Enoch in the Tradition of the Church of Jesus Christ of Latter-Day Saints (Mormonism) -- Part 2 Revisiting James Bruce's "Discovery" and Its Impact -- 8 James Bruce's Illusory "Book of Enoch the Prophet" -- 9 James Bruce and His Copies of Ethiopic Enoch -- 10 A "Rich and Unparalleled Collection": The Afterlives of James Bruce's Manuscripts and Drawings -- 11 When Enoch Left Ethiopia: On Race and Philological (Im)possibilities in the Nineteenth Century -- Part 3 Enoch beyond Europe -- 12 The Reception and Function of 1 Enoch in the Ethiopian Orthodox Tradition -- 13 The Archangel Uriel in 1 Enoch and Other Ethiopian Texts -- 14 Scales of Creation or Scales of Judgment?: Variant Readings for Parables of Enoch 41 and 43 -- 15 Heavenly Exiles and Earthly Outcasts: Enochic Concepts of Hermetic Knowledge and Proscribed Lore in Parabiblica Slavica (Fifteenth-Nineteenth Centuries) -- 16 Enoch as Idrīs in Early Modern Ottoman Sufi Writings: Two Case Studies -- 17 Why Enoch Did Not Die: The Soul Construction of Enoch in the Zohar and Sixteenth-Century Kabbalah -- Appendix The Earliest English Translations and Synopses of Ethiopic Enoch (1770-1820) -- Index.